The Influence of 0.5% Tropicamide on Anterior Segment Parameters With CASIA2 in Emmetropic, Myopic, and Hyperopic Eyes - Lin, Feng; Wang, Yuliang; Liu, Yujia; Qu, Xiaomei; Zhou, Xingtao (Frontiers in Physiology, 2022)
Aim: To evaluate the effects of 0.5% tropicamide on anterior segment parameters with the CASIA2 imaging device in emmetropic, myopic, and hyperopic eyes. Methods: In this prospective study, a total of 125 subjects (34 emmetropic subjects, 57 myopic subjects, and 34 hyperopic subjects) at the Shanghai Eye and ENT Hospital of Fudan University were recruited from June 2021 to September 2021. The 0.5% tropicamide solution was used once every 5 minutes a total of 5 times for cycloplegia. The anterior segment parameters were recorded by CASIA2 before and after cycloplegia. Changes in anterior segment parameters were compared among the three refractive groups. Results: Crystalline lens rise (CLR) and crystalline lens thickness (CLT) significantly decreased in all three refractive groups after cycloplegia (all p<0.01). The anterior radius of lens (ARL) and anterior chamber depth (ACD) significantly increased in all three refractive groups after cycloplegia (all p<0.01). Posterior radius of lens (PRL) significantly increased in hyperopic eyes after cycloplegia (p<0.01) while it remained unchanged in emmetropic eyes and myopic eyes. Central corneal thickness (CCT), anterior chamber width (ACW), lens decentration (LD), and lens tilt (LT) remained unchanged after cycloplegia in all three refractive groups (all p>0.05). Changes in CLR, CLT, ARL, PRL, and ACD in hyperopic eyes were greater than those in emmetropic eyes and myopic eyes (all p<0.05). Conclusion: Apart from various changes in anterior segment parameters after application by 0.5% tropicamide in all three refractive groups, significant changes in CLR, CLT, ARL, PRL, and ACD in hyperopic eyes should be noted for proper clinical interpretation.